Advantages of using larger-diameter pinhole collimator for prompt X-ray imaging during irradiation with carbon ions. (1st September 2022) - Yamamoto, Seiichi; Yabe, Takuya; Akagi, Takashi; Yamaguchi, Mitsutaka; Kawachi, Naoki; Kamada, Kei; Yoshikawa, Akira; Kataoka, Jun
Abstract: Prompt secondary electron bremsstrahlung X-ray (prompt X-ray) imaging using a low-energy X-ray camera is a promising method for observing a beam shape from outside the subject. However, the images measured within short times suffer from statistical noise. Consequently, we performed prompt X-ray imaging with higher sensitivity using a larger-diameter pinhole collimator and compared the results with those of a conventional collimator. Prompt X-ray imaging was conducted during irradiation with pencil beams of 241.5-MeV/n carbon ions to a water phantom. A newly developed X-ray camera with a 4-mm diameter as well as conventional 1.5-mm-diameter pinhole collimators was used for the imaging in list mode, and we compared the prompt X-ray images, energy spectra, and time count rate curves between 1.5-mm-diameter and 4-mm-diameter pinhole collimators. The prompt X-ray images taken with the 4-mm-diameter pinhole collimators had ∼7 times higher sensitivity with 70 % lower offset fractions originating from the prompt gamma photons. Furthermore, the ranges were more precisely estimated with the 4-mm collimator than with the 1.5-mm collimator. The energy spectra showed less contamination by tungsten-characteristic X-rays for the 4-mm pinhole collimator. Even for images measured with 0.1-s intervals, the beam shapes and time count rate curves could be obtained with less statistical noise using the 4-mm-diameter pinhole collimators. The use of the 4-mm-diameter pinhole collimator attached to the X-ray camera had advantages for prompt X-ray imaging with high sensitivity and low background, enabling us to image the beams even with short-time measurements.